2016
DOI: 10.1161/strokeaha.115.011256
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prestroke Vascular Pathology in Long-Term Prognosis After Stroke

Abstract: Background and Purpose-Mortality after stroke remains high for years, mostly because of cardiovascular causes. Given that cardiovascular pathology plays an important role in causing the initial stroke, such prestroke pathology might also influence the prognosis after stroke. Within the population-based Rotterdam Study, we examined the proportion of deaths after stroke that are attributable to pre-existent cardiovascular risk factors before stroke (the population attributable risk). Methods-We examined 1237 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Moreover, patients from PROSCIS-M were better educated, which at least partly explains the higher impact of education on poor outcome. All prognostic factors for death or functional impairment after first-ever ischemic stroke in our cohort are in line with those found in previous studies [ 1 5 , 28 32 ]. Furthermore, we found similar magnitudes of average PAR for age≥75 years (average PAR in PROSCIS-B: 17.29%, PROSCIS-M 20.89%), compared to previous studies applying the same PAR estimation methodology [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, patients from PROSCIS-M were better educated, which at least partly explains the higher impact of education on poor outcome. All prognostic factors for death or functional impairment after first-ever ischemic stroke in our cohort are in line with those found in previous studies [ 1 5 , 28 32 ]. Furthermore, we found similar magnitudes of average PAR for age≥75 years (average PAR in PROSCIS-B: 17.29%, PROSCIS-M 20.89%), compared to previous studies applying the same PAR estimation methodology [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…PAR is a methodological tool to prioritize targets for modification according to their assumed contribution to reduce the outcome of interest, in our case patient’s mortality and morbidity. While different estimation methods were used in previous studies [ 3 , 5 7 ], to the best of our knowledge, this is the first publication that simultaneously assesses and directly compares PAR values obtained by different statistical approaches in a real-life data set. In our analysis, the ranking by magnitudes of PAR was almost similar for all methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 4 , 5 ] Inflammatory proteins might play a significant role in the pathogenesis of stroke. [ 6 ] Intuitively, it seems that inflammation mediators may play an important role in atherothrombotic stroke. Numerous evidence suggested that matrix metalloproteinases (MMPs) are fundamental players in stroke recovery.…”
Section: Introductionmentioning
confidence: 99%